2018
DOI: 10.1002/jcb.27834
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of IGF1, IGF2BP2, and IGFBP3 variants with lymph node status and esophagogastric junction adenocarcinoma risk

Abstract: Esophagogastric junction adenocarcinoma (EGJA) may be associated with obesity and overweight. Thus, any variant in energy metabolism–related gene may influence the development of EGJA. In this study, we recruited 720 EGJA cases and 1541 noncancer controls. We selected IGF2BP2 rs4402960 G > T, rs1470579 A > C, IGF1 rs5742612 A > G and IGFBP3 rs3110697 G > A, rs2270628 C > T and rs6953668 G > A loci and assessed the relationship of these polymorphisms with lymph node status and susceptibility of EGJA. We found… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 42 publications
(118 reference statements)
2
18
0
Order By: Relevance
“…For each locus in BTLA gene, an online χ 2 test was used to assess the Hardy-Weinberg equilibrium (HWE) [25]. The Student t test was performed to deal with continuous variables of demographic characteristics between two groups.…”
Section: Methodsmentioning
confidence: 99%
“…For each locus in BTLA gene, an online χ 2 test was used to assess the Hardy-Weinberg equilibrium (HWE) [25]. The Student t test was performed to deal with continuous variables of demographic characteristics between two groups.…”
Section: Methodsmentioning
confidence: 99%
“…Chen et al suggested that the IGF2BP2 rs4402960 polymorphism T allele may be a protective factor for decreased susceptibility to NSCLC among women [13]. Tang et al found that the IGF2BP2 rs1470579 variant is a protective factor against esophagogastric junction adenocarcinoma [14].…”
Section: Introductionmentioning
confidence: 99%
“…A total of 1541 controls was recruited. The detailed information of the participants was present in our previous study . Each participant was informed of the study purpose and signed a written informed consent.…”
Section: Methodsmentioning
confidence: 99%
“…The detailed information of the participants was present in our previous study. 23 Each participant was informed of the study purpose and signed a written informed consent. In this study, a questionnaire was used to collect demographic data (sex and age), smoking, and drinking history.…”
Section: Subjectsmentioning
confidence: 99%